Skin adnexal tumours in Kano, Northern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background and Objective:Tumours of skin adnexae are an uncommon group of neoplasms that have not been formally studied in our locality. We undertook this reviewto document and evaluate the pattern in Kano, northern Nigeria.Materials and Methods:This is a 10-year (2004-13) retrospective study of all skin adnexal tumours diagnosed at the pathology department of Aminu Kano Teaching Hospital (AKTH), Kano.Results:Ninety-two skin adnexal tumours were diagnosed during the study period, and there was no significant gender predilection - males (49%), females (51%). The overwhelming majority were benign (86%), while malignancies comprised just 14%. Patients ranged from 4 to 90 years of age, peaking in the third and fifth decades. The most common histological types were nodular hidradenoma (17.4%), eccrine poroma (9.8%) and pilomatrixoma (9.8%), with sebaceous carcinoma (5.4%) as the most frequent adnexal malignancy. The tumours were most commonly located in the head and neck region (52%), followed by the trunk (25%) and extremities (23%).Conclusion:Skin adnexal tumours are relatively uncommon in Kano affecting predominantly people in the third and fifth decade without a definitive sex predilection. Most of the tumours showed sweat gland differentiation with nodular hidradenoma and sebaceous gland carcinoma being the most common benign and malignant tumours, respectively.